2019
DOI: 10.3390/c5030044
|View full text |Cite
|
Sign up to set email alerts
|

Waste Coffee Management: Deriving High-Performance Supercapacitors Using Nitrogen-Doped Coffee-Derived Carbon

Abstract: In this work, nitrogen-doped activated carbon was produced from waste coffee powder using a two-step chemical activation process. Nitrogen doping was achieved by treating the coffee powder with melamine, prior to chemical activation. The produced nitrogen-doped carbon resulted in a very high surface area of 1824 m2/g and maintained a high graphitic phase as confirmed by Raman spectroscopy. The elemental composition of the obtained coffee-derived carbon was analyzed using X-ray photoelectron spectroscopy (XPS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The results for C sp at different scan rates, from 20 to 500 mV/s, have been presented in Figure 4 c. The results show that the specific capacitance decreases by increasing the scan rate from 20 to 500 mV/s which can be due to different factors such as pore-size distribution, the presence both of micro- and mesopores, and specific surface area as reported before [ 33 , 34 , 35 , 36 ]. In both S2 and S3, charged nanofibrous structures have more time at lower scan rates to interact with other fibers and pores of T3DN electrodes.…”
Section: Resultssupporting
confidence: 53%
“…The results for C sp at different scan rates, from 20 to 500 mV/s, have been presented in Figure 4 c. The results show that the specific capacitance decreases by increasing the scan rate from 20 to 500 mV/s which can be due to different factors such as pore-size distribution, the presence both of micro- and mesopores, and specific surface area as reported before [ 33 , 34 , 35 , 36 ]. In both S2 and S3, charged nanofibrous structures have more time at lower scan rates to interact with other fibers and pores of T3DN electrodes.…”
Section: Resultssupporting
confidence: 53%
“…Choi et al, reversed the last two steps in the method proposed by Pietrzak et al, and prepared NCM from spent coffee grounds (SCG) and melamine using the following method: pyrolysis (800°C for 2 hours) → reaction with melamine (800°C for 2 hours) → KOH activation (800°C for 2 hours). The XPS results showed that the N was incorporated to the surface of the NCM; moreover, after KOH activation, a significant reduction in the N content occurred, and most of the pyridinic‐N and graphitic‐N vanished 18 …”
Section: Introductionmentioning
confidence: 99%
“…The Sichuan pepper-derived carbon material display reasonably good electrochemical performance with specific capacitance 171 F g −1 at 1 A g −1 without any capacitance loss until 10,000 charging−discharging cycles. KOH activation of coffee powder (waste material) interestingly yielded nitrogen-doped carbon as reported by Gupta and coworkers [148]. For the successful nitrogen doping coffee powder required to treat with melamine prior to the activation.…”
Section: Nanoporous Carbons From Natural Biomassmentioning
confidence: 86%